2011
DOI: 10.1111/j.1750-3841.2011.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Organic Acids to Inactivate Escherichia coli O157:H7, Salmonella Typhimurium, and Listeria monocytogenes on Organic Fresh Apples and Lettuce

Abstract: It is suggested that organic acids have a potential as sanitizers for organic fresh produce. These data may help the organic produce industry provide safe fresh produce for consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 31 publications
(33 reference statements)
3
66
0
2
Order By: Relevance
“…Some considerations regarding authorizations for use on produce in the United States are addressed in Table 1. The insights and quantitative estimates generated in this study will be (Akbas & Olmez, 2007;Choi et al, 2012;Hellstrom et al, 2006;Kim, Kim, & Song, 2009a, 2009bLee et al, 2002;Park, et al, 2011;Rodgers et al, 2004;Ruiz-Cruz et al, 2007;Sagong et al, 2011;Szabo et al, 2003;Yuk, Yoo, Yoon, Marshall, & Oh, 2007;Yuk et al, 2006;Zhang & Farber, 1996) Lactic acid is a direct food ingredient affirmed as generally recognized as safe (GRAS) as an antimicrobial agent, and shall meet the identity, limitations, and specifications described in this authorization ( 21 CFR 184.1061).…”
Section: Chlorine Dioxide~0mentioning
confidence: 98%
“…Some considerations regarding authorizations for use on produce in the United States are addressed in Table 1. The insights and quantitative estimates generated in this study will be (Akbas & Olmez, 2007;Choi et al, 2012;Hellstrom et al, 2006;Kim, Kim, & Song, 2009a, 2009bLee et al, 2002;Park, et al, 2011;Rodgers et al, 2004;Ruiz-Cruz et al, 2007;Sagong et al, 2011;Szabo et al, 2003;Yuk, Yoo, Yoon, Marshall, & Oh, 2007;Yuk et al, 2006;Zhang & Farber, 1996) Lactic acid is a direct food ingredient affirmed as generally recognized as safe (GRAS) as an antimicrobial agent, and shall meet the identity, limitations, and specifications described in this authorization ( 21 CFR 184.1061).…”
Section: Chlorine Dioxide~0mentioning
confidence: 98%
“…Organic acids are generally recognised as safe (GRAS) for use as food ingredients. Some organic acids have been evaluated as sanitisers on fruits and vegetables (Park et al 2011). Malic acid is the dominant acid in apple fruits, accounting for up to 90% of the total organic acids (Wu et al 2007;Zhang et al 2010) and has an important influence on the sour taste of apples.…”
mentioning
confidence: 99%
“…Nascimento and Silva (2010) treated strawberries with different chemical products and observed greater reductions with 4% acetic acid, specifically with reductions of 1.18 and 1.34 log CFU·g -1 for mesophilic aerobic and moulds and yeast. Park et al (2011) observed that after 10 min of treatment in apples, 1 and 2% acid acetic promoted 0.52 to 2.78 log reduction and exhibited significant (p< 0.05) antibacterial effects against Escherichia coli O157:H7, Salmonella Typhimurium and Listeria monocytogenes as compared to the control treatment.…”
Section: Efficiency Of Sanitization Treatments On Natural Contaminantmentioning
confidence: 94%